Tradisi Pemberian Gelar Adat dalam Upacara Perkawinan Pada Masyarakat Komering Desa Rasuan Kecamatan Madang Suku 1 Kabupaten OKU Timur (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2020)
The tradition of giving a customary title is the gift of a customary name that is given to every community who will carry out a marriage where the title given will be carried out by customary stakeholders. The tradition that has become the custom of the Rasuan village, the East 1 OKU tribe is still preserved until now. An interesting thing that will be examined is the traditional title which is given only when the marriage occurs. The customary title in question ia a respect for someone who will carry out a household life with a marriage, therefore they will be given a customary title, which can be said to be a second name. the traditional title tradition has a meaning as a tribute to the ancestors, has a hope and a prayer in a new life.